Improving Access to Banking : Evidence from Kenya - Allen, Franklin; Carletti, Elena; Cull, Robert; Qian, Jun; Senbet, Lemma; Valenzuela, Patricio (World Bank, Washington, DC, 2013)
Using household surveys and bank penetration data at the district-level in 2006 and 2009, this paper examines the impact of Equity Bank -- a leading private commercial bank focusing on microfinance -- on access to banking in Kenya. Unlike other commercial banks in Kenya, Equity Bank pursues distinct branching strategies that target underserved areas and less-privileged households. Equity Bank presence has a positive and significant impact on households' use of bank accounts and bank credit, especially for Kenyans with low income, no salaried job, and less education and those who do not own their own home. The findings are robust to using the district-level proportion of people speaking a minority language as an instrument for Equity Bank presence. It appears that Equity Bank's business model -- providing financial services to population segments typically ignored by traditional commercial banks and generating sustainable profits in the process -- can be a solution to the financial access problem that has hindered the development of inclusive financial sectors in many African countries.